2016
DOI: 10.1002/ptr.5616
|View full text |Cite
|
Sign up to set email alerts
|

Scope of Hydrolysable Tannins as Possible Antimicrobial Agent

Abstract: Hydrolysable tannins (HTs) are secondary metabolites from plants, which are roughly classified into gallotannins and ellagitannins having gallic acid and ellagic acid residues respectively attached to the hydroxyl group of glucose by ester linkage. The presence of hexahydroxydiphenoyl and nonahydroxyterphenoyl moieties is considered to render antimicrobial property to HTs. HTs also show considerable synergy with antibiotics. Nevertheless, they have low pharmacokinetic property. The present review presents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 102 publications
2
59
1
Order By: Relevance
“…In addition, glycosylated phenolic derivatives are present in the extract and are described by some authors as new types of hydrolysable tannins, which exert antimicrobial action by breaking the permeability of the membrane of different microbial strains [61]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, glycosylated phenolic derivatives are present in the extract and are described by some authors as new types of hydrolysable tannins, which exert antimicrobial action by breaking the permeability of the membrane of different microbial strains [61]. …”
Section: Discussionmentioning
confidence: 99%
“…The most active tannins appear to be the most cytotoxic. Several studies have suggested that tannins may interfere with Herpes simplex virus absorption as well as the absorption of HIV and its cytopathic effects (Lipińska et al, ; Ekambaram et al, ). This mechanism seems to be related to the capacity of tannins to bind the viral envelope components.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism seems to be related to the capacity of tannins to bind the viral envelope components. Furthermore, ellagitannins and several proanthocyanidins have been demonstrated to be potent reverse transcriptase inhibitors (Ekambaram et al, ). One hydrolyzable tannin, ellagic acid, also shows specific antiviral activity against hepatitis B virus (HBV) by inhibiting HBeAg secretion in HBV‐infected cells (Marín et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tannins are water‐soluble polyphenolic compounds arising from the metabolism of plants. Tannins have been reported to possess antioxidant, antimicrobial and anti‐inflammatory capacities (Ekambaram, Perumal, & Balakrishnan, ; Liu, Zhou, Tong, & Vaddella, ; Redondo, Chacana, Dominguez, & Fernandez‐Miyakawa, ). Previous studies found that dietary chestnut tannin (CT), the extracts from Castanea sativa rich in hydrolysable tannins, improved the performance of rabbits (Liu et al., ) and broilers under normal or high temperature conditions (Dong et al., ; Schiavone et al., ) and altered the basal metabolism of heat‐stressed broilers (Xiong et al., ).…”
Section: Introductionmentioning
confidence: 99%